Intranasal "painless" human Nerve Growth Factor [corrected] slows amyloid neurodegeneration and prevents memory deficits in App X PS1 mice. - Simona Capsoni (Public Library of Science (PLoS), 2012)
Nerve Growth Factor (NGF) is being considered as a therapeutic candidate for Alzheimer's disease (AD) treatment but the clinical application is hindered by its potent pro-nociceptive activity. Thus, to reduce systemic exposure that would induce pain, in recent clinical studies NGF was administered through an invasive intracerebral gene-therapy approach. Our group demonstrated the feasibility of a non-invasive intranasal delivery of NGF in a mouse model of neurodegeneration. NGF therapeutic window could be further increased if its nociceptive effects could be avoided altogether. In this study we exploit forms of NGF, mutated at residue R100, inspired by the human genetic disease HSAN V (Hereditary Sensory Autonomic Neuropathy Type V), which would allow increasing the dose of NGF without triggering pain. We show that "painless" hNGF displays full neurotrophic and anti-amyloidogenic activities in neuronal cultures, and a reduced nociceptive activity in vivo. When administered intranasally to APPxPS1 mice ( n = 8), hNGFP61S/R100E prevents the progress of neurodegeneration and of behavioral deficits. These results demonstrate the in vivo neuroprotective and anti-amyloidogenic properties of hNGFR100 mutants and provide a rational basis for the development of "painless" hNGF variants as a new generation of therapeutics for neurodegenerative diseases.